Determinant Model of Case Method and Team-Based Project Learning Models Through Collaborative Class Strategies with Off-Campus Partners - Muhammad Harlanu (Journal of Innovation in Educational and Cultural Research, 2024)
Case method and team-based learning are two key performance indicators (KPIs) implemented by the Ministry of Education and Culture Number 3/M/2021. Case-method and team-based projects are learning that is imposed on students to improve students’ critical thinking skills, solve problems, find solutions, and develop communication skills. This learning is also helpful for lecturers to improve higher abilities and skills. This research aims to test the Determinant Model for applying the Case Method and Team-Based Project in the Key Performance Indicator (KPI) Achievement Policy for Higher Education. This research used quantitative methods with a survey design. Data collection used a research instrument in the form of a questionnaire, which had been declared valid and reliable. Furthermore, the data collected was analyzed using descriptive and inferential statistics using path analysis techniques. The research concludes that using the case method model in higher education is significantly related to improving the key performance indicators for higher education.